1994
DOI: 10.1128/mcb.14.1.700
|View full text |Cite
|
Sign up to set email alerts
|

Maf nuclear oncoprotein recognizes sequences related to an AP-1 site and forms heterodimers with both Fos and Jun.

Abstract: The v-maf oncogene, identified from AS42 avian retrovirus, encodes a nuclear bZip protein. To elucidate the molecular mechanism of cell transformation induced by this oncogene, we determined the specific binding sequences of its product. Maf protein recognized two types of relatively long palindromic consensus sequences, TGCTGACTCAGCA and TGCTGACGTCAGCA, at roughly equal efficiency. The middle parts of these Maf-binding sequences completely match with two binding sequences for AP-1 transcription factor, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
367
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(381 citation statements)
references
References 73 publications
11
367
0
2
Order By: Relevance
“…On the other hand, nucleotide )130 "A" in RIPI obviously differs from nucleotide "G" in the other insulin promoters and in the MARE sequence. As we have demonstrated in this paper and as others have reported previously [22,24], "G" is crucial for Maf activity. This difference in the RIPI must be the reason why the Mafs did not activate the RIPI reporter in our experiments.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, nucleotide )130 "A" in RIPI obviously differs from nucleotide "G" in the other insulin promoters and in the MARE sequence. As we have demonstrated in this paper and as others have reported previously [22,24], "G" is crucial for Maf activity. This difference in the RIPI must be the reason why the Mafs did not activate the RIPI reporter in our experiments.…”
Section: Discussionsupporting
confidence: 87%
“…These results indicate that the responsible elements for Maf activation are located between )126 and )101 of RIPII. Since this region includes the RIPE3b element, which contains the Maf recognition element (MARE) like sequence [22] (Fig. 6E), we focused on the core site ()119 to )113) of the RIPE3b element as the Maf binding sequence.…”
Section: Ripe3b Is the Target Site Of Mafa And Mafbmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, numerous members, including Maf-B, c-Maf, LMaf, S-Maf, and NRL, have been isolated, and they exhibit specific tissue expression patterns (reviewed in Blank and Andrews, 1997;Kajihara et al, 2001;Reza and Yasuda, 2004). These Maf proteins can form homodimers or heterodimers of the same family and also heterodimerize with c-Fos or c-Jun to exert their functions through palindromic recognition elements known as T-MARE (Kataoka et al, 1994;Kerppola and Curran, 1994;Matsushima and Sakai, 1998). Contrarily, our study, however, showed that the proximal minimal Ϫ90/ ϩ61-bp promoter, which contains a single conserved Maf binding site, is sufficient to transactivate the human ␤B1-crystallin gene.…”
Section: Discussionmentioning
confidence: 99%